2018
DOI: 10.4103/ccd.ccd_749_17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of plaque control with novel pediatric oral hygiene need station (modified oral irrigation device) as compared with manual brushing and flossing: Randomized controlled pilot trial

Abstract: Background:Establishing good hygiene habits are valuable for present and future oral health. Below 6 years, tooth brushing should be performed by parents, as increasing dexterity and cognition may permit supervised brushing until the child is capable of independent brushing.Aim and Objectives:The aim of the present study was to evaluate the effectiveness of modified oral irrigation device in children in terms of plaque control and to compare the effectiveness of plaque control with manual brushing with the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
6
0
3
Order By: Relevance
“…Less than half of the parents of these children helped their children brush their teeth at night or before sleep. Murthy et al [25] reported that, for children under six years of age, tooth-brushing should be performed by parents. Behaviors for preventing SECC include parental assistance in tooth-brushing at night and the use of dental floss.…”
Section: Discussionmentioning
confidence: 99%
“…Less than half of the parents of these children helped their children brush their teeth at night or before sleep. Murthy et al [25] reported that, for children under six years of age, tooth-brushing should be performed by parents. Behaviors for preventing SECC include parental assistance in tooth-brushing at night and the use of dental floss.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 90% pocket penetration was achieved when probing depths were ≤6 mm [63]; oral irrigators were found to penetrate on average about half the depth of pockets, with the greatest penetration for pockets 0–3 mm and >7 mm [64]. The use of an oral irrigator does not appear to require any special motor skill, as demonstrated in 5.5–6.5-year-old children [65].…”
Section: Oral Irrigatorsmentioning
confidence: 99%
“…ECC can be prevented through healthy eating habits, brushing twice daily and flossing daily, receiving regular preventive dental services, and community-level behavioral education [ 13 , 19 , 20 ]. Studies on the prevention of ECC have shown that community-level education about dietary habits and dental care is as important as measures taken every day at home (i.e., brushing and flossing) [ 21 , 22 ]. Several studies have shown that the etiology of ECC is often multifactorial and associated with multiple risk factors [ 23 ].…”
Section: Introductionmentioning
confidence: 99%